Concepts and applications of finite element analysis (John Wiley & Sons, INC, 2002)
This book has been thoroughly revised and updated to reflect developments since the third edition, with an emphasis on structural mechanics. Coverage is up-to-date without making the treatment highly specialized and mathematically difficult. Basic theory is clearly explained to the reader, while advanced techniques are left to thousands of references available, which are cited in the text.